Genes and pathways downstream of telomerase in melanoma metastasis - Bagheri, Sepideh (National Academy of Sciences, 2006)
Recent studies have demonstrated a role for telomerase in driving tumor progression, but its mechanism of action remains unclear. Here we show that stable, ribozyme-mediated suppression of mouse telomerase RNA reduced telomerase RNA expression, telomerase activity, and telomere length, which significantly reduced tumor invasion and metastatic potential. Our studies reveal that previously unidentified effects of telomerase may mediate its tumor-promoting effects. First, reducing telomerase activity induced a more dendritic morphology, accompanied by increased melanin content and increased expression of tyrosinase, a key enzyme in melanin biosynthesis. Second, gene expression profiling revealed that telomerase targeting down-regulated expression of several glycolytic pathway genes, with a corresponding decrease in glucose consumption and lactate production. Thus, telomerase activity controls the glycolytic pathway, potentially altering the energy state of tumor cells and thereby modulating tyrosinase activity and melanin production. These studies have important implications for understanding the mechanisms by which telomerase promotes tumor invasion and metastasis.